ISOLATION AND CHARACTERIZATION OF ANTIOXIDANT COMPOUND FROM JAYANTI LEAVES EXTRACT SESBANIA SESBAN L. MERRIL - Nurlaela Fitriansyah, Sani
Background and Objectives : Indonesia is a tropical country which has wide biological diversity. Many research has shown that natural medicines has so many potency. Antioxidant is one potency of nature that is being concerned nowdays. Jayanti is widely distributed in tropical country, especially in Indonesia, and has been used traditionally by Indonesian people as remedy for cold, cough, irregular menstruation, and renal infection. Methanolic extract of jayanti flower and ethanolic extract of jayanti leaves showed antioxidant activity. This research aim to determine the antioxidant activity from jayanti extracts with different polarities using DPPH free radical scavenging method, correlation between total flavonoid, total phenol, total carotenoid and DPPH scavenging activity, and to isolate compound with antioxidant activity from jayanti leaves extracts. Method: Extraction was done using reflux method with three solvent in increasing polarity. The qualitative antioxidant activity was done using TLC and quantitatively using spectrophotometry UV-visible. The n-hexane and ethanol extract were selected for fractination. Extracts were separated using vacum liquid chromatography (VLC) with gradient elution (n-hexane-ethyl acetate) and (ethyl acetate-methanol) and further separated using radial chromatography. Purification by washing was done to isolate from n-hexane fraction (isolate A) and paper chromatography (PC) for isolate from ethanolic extract (isolate B). The purification was tested by TLC with three different mobile phase and 2 dimensional TLC and. Isolate was characterized using TLC, using H2S04 10% spraying reagent, sitroboric acid, FeC13 1%, 2 dimensional PC, and shift reagents. Resylts: Ethanolic extract had the highest DPPH scavenging activity (52,87%), lowest IC50 4,12 ug/mL, and highest total phenolic (5,18 g GAE/IOO g) and total flavonoid (4,56 g QE/IOO g), meanwhile the n-hexane extract has the highest total carotenoid (4,56 g BET/ 100g). Total phenolic, total flavonoid, and total carotenoid in n-hexane, ethyl acetate and ethanol extract were significantly different (p<0,05). Total phenolic and carotenoid had positive and high correlation with DPPH scavenging activity. One antioxidant compound from n-hexane extract had been isolated as dark red crystal and one needle crystal had been isolated from ethanolic extract. From TLC pattern and spectrophotometry UV-vis with ß-carotene standard, isolate A was spposed to be ß-carotene. Isolate B which had RI in 349 nm and 12 266 nm, predicted to be flavonol-glicoside. Conclusion: Ethanolic extract had the highest antioxidant activity and the lowest IC50 compared with IT-hexane and ethyl acetate extract. Total phenolic and carotenoid had positive and high correlation with DPPH scavenging activity. Antioxidant compound(A) from Il-hexane extract was supposed to be ß-carotene and (B) from ethanolic extract was predicted to be 5,7,4'-trihidroxy-flavonol-3-O-glycoside.